Analisis Penyebab Penolakan Klaim Nasabah di PT Asuransi Umum Bumiputra Muda 1967 (Cabang Medan) - Febrianti, Yulia; Batubara, Maryam (VISA: Journal of Vision and Ideas, 2024)
The aim of this research is to analyze the reasons behind the rejection of claims at PT Asuransi General Bumiputra Muda Medan Branch. The analytical method used is a qualitative descriptive technique that uses interviews to collect data on ten informants who work at PT Asuransi General Bumiputra Muda Medan Branch. Based on research findings, the causes of lost claims at PT Asuransi Jenderal Bumiputra Muda Medan Branch include incomplete documentation, inaccurate information in insurance claims, police investigations, delays in processing claims, and handling errors. The implications of this research include that PT Asuransi General Bumiputra Muda Medan Branch must improve communication with customers regarding the insurance claims process and strengthen internal processes to prevent fraud.